Post-Covid-19 Teacher Training: The Trends that Are to Stay - Burlakova, Mariya; Mikhailov, Alexey (International Dialogues on Education Journal, 2022)
The COVID-19 pandemic has had a significant impact on Shuya University. For a year, the students had to do all their academic work online, which has turned out to be both intellectual and emotional lockdown for them. Now that the students are back at the campus, there has been a significant fall in the students’ motivation to study and a rise in the withdrawals from the courses. The escape into the Internet and the absence of face-to-face communication with peers and professors have disorientated the students and have had an impact on their academic integrity. Yet, the crisis has showed some positive implications that result from revealing the potential of virtual learning environments with new methods of interactions between students and teachers and changing the overall way of governing the university. The authors present an overview of a few “new-normal” academic trends that emerged after the pandemic outbreak and seem to have set in at the provincial Russian university in the city of Shuya.